Implementasi Algoritma Fisher Yates Shuffle pada Bagan Undian Peserta Pertandingan Pencak Silat - Maulana Muhammad Rizky; Asriyanik Asriyanik; Lelah Lelah (Progresif: Jurnal Ilmiah Komputer, 2021)
Abstract. The manual lottery system in determining the scheme of contestants in the pencak silat championship causes the process to be ineffective and inefficient, so information technology assistance is needed. This paper presents an application model for determining the scheme of participants in a pencak silat match using a participant lottery chart system assisted by the Fisher Yates Shuffle algorithm. The application is tested using the blackbox testing method. The results of the application test in the process of randomizing the lottery of match participants showed a more effective and efficient process.Keywords: Fisher Yates Shuffle Algorithm, Randomization, Participant Lottery Chart, Pencak SilatAbstra. Sistem undi manual dalam menentukan skema peserta pertandingan pada kejuaraan pencak silat, menyebabkan proses menjadi tidak efektif dan tidak efisien, sehingga diperlukan bantuan teknologi informasi. Paper ini menyajikan model aplikasi untuk penentuan skema peserta pertandingan pencak silat menggunakan sistem bagan undian peserta berbantuan algoritma Fisher Yates Shuffle. Aplikasi diuji menggunakan motode pengujian blackbox testing. Hasil uji aplikasi dalam proses pengacakan undian peserta pertandingan menunjukkan proses yang lebih efektif dan efisien.Kata kunci: Algoritma Fisher Yates Shuffle, Pengacakan, Bagan Undian Peserta, Pencak Silat